Expression of NF-κB p50 in tumor stroma limits the control of tumors by radiation therapy. - Marka R Crittenden (Public Library of Science (PLoS), 2012)
Radiation therapy aims to kill cancer cells with a minimum of normal tissue toxicity. Dying cancer cells have been proposed to be a source of tumor antigens and may release endogenous immune adjuvants into the tumor environment. For these reasons, radiation therapy may be an effective modality to initiate new anti-tumor adaptive immune responses that can target residual disease and distant metastases. However, tumors engender an environment dominated by M2 differentiated tumor macrophages that support tumor invasion, metastases and escape from immune control. In this study, we demonstrate that following radiation therapy of tumors in mice, there is an influx of tumor macrophages that ultimately polarize towards immune suppression. We demonstrate using in vitro models that this polarization is mediated by transcriptional regulation by NFκB p50, and that in mice lacking NFκB p50, radiation therapy is more effective. We propose that despite the opportunity for increased antigen-specific adaptive immune responses, the intrinsic processes of repair following radiation therapy may limit the ability to control residual disease.